The importance of iron and copper accumulation in the pathogenesis of non-alcoholic steatohepatitis - Kemal AKIN,; Ali Reşit BEYLER,; Muhsin KAYA,; Esra ERDEN, (Turkish Journal of Gastroenterology, 2019)
-